The epiknowledge of socially responsible innovation. (May 2014) - Dove, Edward S; Özdemir, Vural
<x xml:space="preserve">Abstract</x> A comment on "The DNA of Socially Responsible Innovation" <boxed-text content-type="graphic" id="embr201438683-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>